Assessment of the level of knowledge about physical therapy approach in pelvic floor dysfunctions in women in the city of Santarém-PA (Research, Society and Development, 2023)
Objective: the objective of the research was to evaluate the level of knowledge of women in the municipality of Santarém, regarding the dysfunctions and treatment of pelvic dysfunctions. Methods: this is a field research, where a questionnaire was applied remotely, through an electronic form, followed by the sending of educational material on the subject. Results and discussion: after analyzing the results, it was possible to observe that the patients, despite reporting voiding dysfunctions, or having already gone through the pregnancy process, do not have knowledge about the treatment for these dysfunctions, or if they do, they do not have access to treatment. Conclusion: it is concluded that pelvic dysfunctions are present in the researched sample, but it is necessary to reinforce the importance of guidance and health, and also to favor access to treatment both at the private and public health levels.